Determinants of mortality and prolonged hospital stay among dengue patients attending tertiary care hospital: a cross-sectional retrospective analysis - Yusra Habib Khan; Tauqeer Hussain Mallhi; Amer Hayat Khan; Azmi Sarriff; Azreen Syazril Adnan (BMJ Open, 2017)
Objectives Dengue imposes substantial economic, societal and personal burden in terms of hospital stay, morbidity and mortality. Early identification of dengue cases with high propensity of increased hospital stay and death could be of value in isolating patients in need of early interventions. The current study was aimed to determine the significant factors associated with dengue-related prolonged hospitalisation and death.Design Cross-sectional retrospective study.Setting Tertiary care teaching hospital.Participants Patients with confirmed dengue diagnosis were stratified into two categories on the basis of prolonged hospitalisation (≤3 days and >3 days) and mortality (fatal cases and non-fatal cases). Clinico-laboratory characteristics between these categories were compared by using appropriate statistical methods.Results Of 667 patients enrolled, 328 (49.2%) had prolonged hospitalisation. The mean hospital stay was 4.88±2.74 days. Multivariate analysis showed that dengue haemorrhagic fever (OR 2.3), elevated alkaline phosphatase (ALP) (OR 2.3), prolonged prothrombin time (PT) (OR 1.7), activated partial thromboplastin time (aPTT) (OR 1.9) and multiple-organ dysfunctions (OR 2.1) were independently associated with prolonged hospitalisation. Overall case fatality rate was 1.1%. Factors associated with dengue mortality were age >40 years (p=0.004), secondary infection (p=0.040), comorbidities (p<0.05), acute kidney injury (p<0.001), prolonged PT (p=0.022), multiple-organ dysfunctions (p<0.001), haematocrit >20% (p=0.001), rhabdomyolosis (p<0.001) and respiratory failure (p=0.007). Approximately half of the fatal cases in our study had prolonged hospital stay of greater than three days.Conclusions The results underscore the high proportion of dengue patients with prolonged hospital stay. Early identification of factors relating to prolonged hospitalisation and death will have obvious advantages in terms of appropriate decisions about treatment and management in high dependency units.